Empowering local governments: Evidence from rural land tax decentralization - Pedro Henrique Cavalcanti; Renata Motta Café (Inter-American Development Bank (IDB), 2025)
This paper examines the fiscal and extra-fiscal effects of decentralizing the collection of Brazil's rural land tax from the federal level to local governments. Using a difference-in-differences research design, we assess the impact of local tax enforcement on revenue, land use, and environmental outcomes. Decentralization led to sustained revenue gains, increased agricultural production, expanded reported environmental protection areas, and slightly decreased land concentration. Our findings highlight the role of property taxation as a policy instrument for environmental conservation and sustainable development.
Keywords: H23; H30; H77; 330; fiscal decentralization; extra-fiscality; land use; sustainable develop-ment; rural property tax